(untitled) (Agronomy Journal of Nepal, 2013)
Farmers’ right is considered important to farmers for conservation of agro biodiversity and fostering innovations in agriculture. This paper aims to present findings of the stakeholder survey on the perceptions of farmers’ rights and conservation of agro biodiversity in Nepal. The study was carried out in 2006-2007 employing combination of personal interviews, focussed group discussions and consultation meetings to collect perceptions of diverse group of stakeholders (n=124) on issues related to farmers’ rights and conservation of agrobiodiversity. Stakeholders interviewed were farmers, representatives of CBOs, I/NGOs, private sectors, and public sector R & D organisations including government planners. Findings revealed that agrobiodiversity conservation is important to ensuring food security and improving the livelihood of people. Stakeholders have high priority to protect rights of farmers and local communities to conserve rich biodiversity of agriculture. Farmers’ right to seeds, traditional knowledge, benefit sharing and participating in decision makings are their important rights perceived by the stakeholders. A large proportion of stakeholders opined that farmers should be given legal ownership rights to genetic resources and to be involved in sharing benefits arising out of the commercialization of genetic resources. Both governments and farmers should be the main stakeholders for claiming ownerships, facilitating access to genetic resources and sharing benefits arising out from the commercialization of the agrobioresources. Options for establishing institutional mechanisms for ensuring farmers’ rights and conservation of agrobiodiversity are suggested both at the local and national level as well. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7517 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.12-23